2021
DOI: 10.33963/kp.a2021.0129
|View full text |Cite
|
Sign up to set email alerts
|

The burden of cardiovascular risk factors among seniors with congenital heart disease: A single tertiary center experience

Abstract: Background:The number of adults with congenital heart disease (ACHD) surviving to old age is increasing worldwide. Acquired cardiovascular comorbidities may complicate the course and treatment of the underlying congenital disease and worsen the prognosis. Aims:The study aimed to assess the burden of cardiovascular (CV) risk factors among elderly patients with ACHD. Methods:A retrospective analysis of data on all patients ≥60 years of age hospitalized in a tertiary clinic for ACHD was performed from July 2013 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…The prevalence of HTN in patients with ACHD was found to be 30-60% [9][10][11]41]. Comorbidities such as HTN and vascular disease were mainly present in patients older than 40 years [9][10][11]28,41]. Previous studies of adults undergoing transcatheter ASDC reported the prevalence of HTN in 4-12% in patients aged <30 years [22,26,31], 12-25% in patients aged 40-60 years [28,29], and 25-61% in patients >60 years old [11,27,28,30].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The prevalence of HTN in patients with ACHD was found to be 30-60% [9][10][11]41]. Comorbidities such as HTN and vascular disease were mainly present in patients older than 40 years [9][10][11]28,41]. Previous studies of adults undergoing transcatheter ASDC reported the prevalence of HTN in 4-12% in patients aged <30 years [22,26,31], 12-25% in patients aged 40-60 years [28,29], and 25-61% in patients >60 years old [11,27,28,30].…”
Section: Discussionmentioning
confidence: 93%
“…Adults with secundum ASD, especially older, can present a higher morbidity and mortality associated with the late presentation of ASD and an increased prevalence of comorbidities with advancing age. The prevalence of HTN in patients with ACHD was found to be 30-60% [9][10][11]41]. Comorbidities such as HTN and vascular disease were mainly present in patients older than 40 years [9][10][11]28,41].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations